Policies for Industrial Progress in Developing Countries - Cody, John; Hughes, Helen; Wall, David (New York : Published for the World Bank [by] Oxford University Press, 1980)
This book focuses on the identification of consistent and effective industrialization policies within practical constraints.
Includes bibliographies and index.
osa; 28/6/17
Loans
Keywords: Industrialization; Developing countries; Underdeveloped area - Econpmic policy